Multi‐Point Measurements of the Plasma Properties Inside an Aurora From the SPIDER Sounding Rocket. Issue 7 (20th July 2021) - Giono, Gabriel; Ivchenko, Nickolay; Sergienko, Tima; Brändström, Urban
Abstract: The Small Payloads for Investigation of Disturbances in Electrojet by Rockets (SPIDER) sounding rocket was launched on February 2nd, 2016 (21:09 UT), deploying 10 free falling units (FFUs) inside a westward traveling auroral surge. Each FFUs deployed spherical electric field and Langmuir probes on wire‐booms, providing in situ multi‐point recordings of the electric field and plasma properties. The analytical retrieval of the plasma parameters, namely the electron density, electron temperature and plasma potential, from the Langmuir probe measurements was non‐trivial due to sheath effects and detailed explanation are discussed in this article. An empirical assumption on the sheath thickness was required, which was confirmed by simulating the plasma environment around the FFU using the Spacecraft Plasma Interaction Software (SPIS). In addition, the retrieved electron density and temperature are also in agreement with the simultaneous incoherent scatter radar measurements from the EISCAT facility. These two independent confirmations provided a good level of confidence in the plasma parameters obtained from the FFUs, and events observed during the flight are discussed in more details. Hints of drift‐wave instabilities and increased currents inside a region of enhanced density were observed by the FFUs. Plain Language Summary: This articles presents the measurements recorded by the SPIDER sounding rocket in 2016. The rocket ejected 10 free falling units inside an aurora. Each units was equipped with instruments to measure the plasma properties (density and temperature) and local electric and magnetic fields. Several technical issues occurred during the flight, limiting the usable data to only two of the units. Nonetheless, the article presents the plasma properties recorded along the trajectory of these two units, as well as comparison with plasma simulation and ground‐based observation of the aurora, with cameras and radar. This provided a complete picture of the event. Although no propagating waves were observed between the two units, some interesting plasma layers with possible turbulent regimes are discussed. In conclusion, the article demonstrates the potential of multi‐point measurements for auroral study, in particular for investigating waves and instabilities. Key Points: The multi‐point measurements from SPIDER sounding rocket allowed the study of auroral multi‐scale processes, dynamics and turbulence A combination of in‐situ and remote ground‐based instruments provided insight on the dynamics and topography of an overdense plasma layer A hybrid plasma simulation was used to confirm the analytically retrieved plasma parameters in a intermediate Langmuir probe sheath regime